2019
DOI: 10.1002/jcla.22972
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐2 provides no incremental predictive value for the presence of obstructive coronary artery disease over N‐terminal pro‐brain natriuretic peptide

Abstract: BackgroundUsing circulating biomarkers as a noninvasive method to assist the evaluation of coronary artery disease (CAD) is beneficial for reducing the unnecessary diagnostic cardiac catheterization. This study aimed to assess the predictive role of angiopoietin‐2 (Ang‐2) for the presence of obstructive coronary stenosis as compared with N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) in patients with symptoms of CAD.MethodsThe study enrolled 222 consecutive symptomatic patients who underwent elective dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…All eligible patients diagnosed with OSA who underwent coronary angiography were classified as patients with or without CAD. CAD was defined as stenosis ≥ 50% of the left main coronary artery or stenosis ≥ 70% of a major epicardial vessel (left anterior descending artery, left circumflex artery, or right coronary artery) [ 9 ]. A final total of 327 participants were consecutively enrolled, including 271 patients with OSA and 56 non-OSA controls.…”
Section: Methodsmentioning
confidence: 99%
“…All eligible patients diagnosed with OSA who underwent coronary angiography were classified as patients with or without CAD. CAD was defined as stenosis ≥ 50% of the left main coronary artery or stenosis ≥ 70% of a major epicardial vessel (left anterior descending artery, left circumflex artery, or right coronary artery) [ 9 ]. A final total of 327 participants were consecutively enrolled, including 271 patients with OSA and 56 non-OSA controls.…”
Section: Methodsmentioning
confidence: 99%
“…We did not find a correlation between plasma concentrations of ANGPT1 or ANGPT2 and BNP in either IHF or NIHF patients. In contrast, a recent study reported a significant correlation between serum concentrations of ANGPT2 and NT-proBNP in more than 200 patients that had undergone diagnostic cardiac catheterization [73]. Several explanations can justify these apparently different results.…”
Section: Discussionmentioning
confidence: 89%
“…Given the fact that our study subjects were in a non-acute condition and scheduled for elective procedure, the relatively low circulating Ang-2 levels, which were insensitive for the discrimination of vulnerable coronary plaque, might have contributed to the negative results in this study. Since the circulating Ang-2 levels are influenced by many factors, including cardiac function [34], renal function [35], and various inflammatory conditions [11], the predictive efficiency of Ang-2 for PMI might be compromised. In addition, in this study, we used high-sensitivity troponin assays that allowed detection of a minuscule damage to myocardial tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, we failed to provide an explanation regarding the association of preoperative NT-proBNP levels with PMI occurrence. Given the multiple clinical application values of NT-proBNP in different scenarios beyond heart failure [34,39,40], further large studies need to be conducted to explore and verify its precise cut-off point in predicting PMI.…”
Section: Discussionmentioning
confidence: 99%